Robotic Cholecystectomy: First Experience in Baltic Countries - Deduchovas, Olegas; Samalavičius, Narimantas Evaldas (Lietuvos chirurgija, 2019)
In this retrospective study we report the first series of robotic cholecystectomies in Baltic countries. From Nov 2018 to Feb 2019, 13 robotic cholecystectomies were performed in Klaipėda University Hospital using the Senhance (TransEnterix) robotic system. Patients were diagnosed with symptomatic gallstone disease and had no life-threatening co-morbidities. We retrospectively investigated patient demographics and pre-, peri- and postoperative data. Five male and eight female patients were included in this study (n = 13). Mean age was 46 years (range 26–72); mean BMI was 26.7 kg/m² (range 21.1–37.7). Mean docking time was 18 min (range 8–27), and mean operative time was 85 min (range, 70–150). There were no conversions to standard laparoscopy or open surgery. There were no intra-operative complications. There was one post-operative bleeding from the gallbladder bed and subhepatic hematoma, successfully treated by laparoscopy. This study demonstrates the feasibility of robotic surgery in performing minimally invasive cholecystectomies.